Residual influence of organic materials, crop residues, and biofertilizers on performance of succeeding mung bean in an organic rice-based cropping system - Mohammadreza Davari; Shri Niwas Sharma; Mohammad Mirzakhani (International Journal of Recycling of Organic Waste in Agriculture)
Background: The present investigation was undertaken to assess the residual influence of organic materials and biofertilizers applied to rice and wheat on yield, nutrient status, and economics of succeeding mung bean in an organic cropping system. The field experiments were carried out on the research farm of IARI, New Delhi during crop cycles of 2006 to 2007 and 2007 to 2008 to study the effects of residual organic manures, crop residues, and biofertilizers applied to rice and wheat on the performance of succeeding mung bean. The experiment was laid out in a randomized block design with three replications. Treatments consisted of six combinations of different residual organic materials, and biofertilizers included residual farmyard manure (FYM) and vermicompost (VC) applied on nitrogen basis at 60 kg haâ1 to each rice and wheat crops, FYM + wheat and rice residues at 6 t haâ1 and mung bean residue at 3 t haâ1 in succeeding crops (CR), VC + CR, FYM + CR + biofertilizers (B), VC + CR + B, and control (no fertilizer applied). For biofertilizers, cellulolytic culture, phosphate-solubilizing bacteria and Rhizobium applied in mung bean. Results: Incorporation of crop residue significantly increased the grain yield of mung bean over residual of FYM and VC by 25.5% and 26.5%, respectively. The combinations of FYM + CR + B and VC + RR + B resulted in the highest increase growth and yield attributing characters of mung bean and increased grain yield of mung bean over the control by 47% and net return by 27%. Conclusions: The present study thus indicate that a combination of FYM + CR + B and VC + CR + B were economical for the nutrient need of mung bean in organic farming of rice-based cropping system.